Evaluation of Leuconostoc mesenteroides YML003 as a probiotic against low‐pathogenic avian influenza (H9N2) virus in chickens - Seo, B.J; Rather, I.A; Kumar, V.J.R; Choi, U.H; Moon, M.R; Lim, J.H; Park, Y.H (Journal of applied microbiology, 2012)
Aim: The aims of the study were to isolate anti‐H9N2 bacteria from Korean Kimchi isolates and to evaluate its performance in cell line, egg and in specific pathogen‐free (SPF) chickens. Methods and Results: Using Madin–Darby canine kidney (MDCK) cell line, 220 bacterial isolates were screened and the isolate YML003 was selected having pronounced antiviral activity against H9N2 virus. This isolate was identified as Leuconostoc mesenteroides by 16S rRNA gene sequencing. Anti‐H9N2 activity of the strain was also evaluated by hemagglutination assay. Leuconostoc mesenteroides YML003 was assessed for its survival in gastric juice and 5% bile acid and the antibiotic susceptibility. Both live and heat‐killed cells were selected for in vivo chicken feeding experiment. Body weight, immune index, serobiochemical parameters and splenic IFN‐γ production were assessed during selected intervals. Viral population in the trachea and cloacae were calculated by quantitative real‐time reverse transcriptase PCR (qRT‐PCR). Conclusions: Leuconostoc mesenteroides YML003 exhibited anti‐H9N2 activity both in in vitro cell line as well as in vivo SPF Chickens. Significance and Impact of the Study: This is a primary report on the anti‐H9N2 activity by a Leuconostoc strain. Amid the increasing reports of avian influenza virus occurrence resulting in severe losses to the poultry industry, prophylactic administration of such probiotic strains are highly significant.